Pengaruh Partisipasi Anggaran, Akuntabilitas Publik dan Gaya Kepemimpinan Terhadap Kinerja Manajerial Pada Organisasi Perangkat Daerah Kabupaten Bangli - Luh Putu Widyasari Dewi; Ida I Dewa Ayu Manik Sastri; I Ketut Puja Wirya Sanjaya (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
This study aims to examine the effect of budgetary participation on managerial performance, to examine the effect of public accountability on managerial performance and to examine the effect of leadership style on managerial performance in the Bangli Regency Regional Apparatus Organization. The population in this study were people who served in the managerial performance of the Regional Apparatus Organization of Bangli Regency and the sampling used the saturated sampling method, namely a number of 65 respondents. The type of data is quantitative data with the primary data source in the form of a questionnaire. The analysis technique used is multiple linear regression analysis, t test, F test and analysis of the coefficient of determination using SPSS version 23 For Windows. The results showed that budget participation had a positive and significant effect on managerial performance, public accountability had a positive and significant effect on managerial performance and leadership style had a positive and significant effect on managerial performance in the Bangli Regency Regional Apparatus Organization. The influence of the variable budget participation, public accountability and leadership style is 94.3%, while the remaining 5.7% is influenced by other variables not discussed in this study.